Association between nitric oxide and cancer and stroke risk: a meta-analysis - Tualeka, Abdul Rohim; Jalaludin, Juliana; Gasana, Janvier; Sopian, Nor Ashikin; Chao, How Ran; Yusmaidie, Mohd; Perumal, Velu; Zurimi, Suardi; Rahmawati, Pudji; Ahsan, Ahsan; Novianti, Salsabila (Taylor & Francis Group, 2024)
Background: Numerous case-control studies have been carried out to test the mechanism by which nitric oxide, specifically the polymorphism 894G>T in the eNOS gene, or endothelial nitric oxide synthase, raises the possibility of stroke and cancer. This meta-analysis aimed to describe the correlation between cancer and stroke risk with nitric oxide (eNOS 894G>T polymorphism). Methods: A comprehensive search was conducted on various digital databases, including Science Direct, PubMed, and Google Scholar, for articles published between 2012-2023. All related studies were collected and analysed to observe the published results. Results: The meta-analysis included a total of fifteen case-control studies. These studies involved 3,019 cases (2,013 cancer and 1,006 strokes) and 3,333 controls (2,187 to evaluate cancer risk and 1,146 to evaluate stroke risk) overall. This study found that the GG versus GT+TT genotype of eNOS 894G>T polymorphism was significantly positively correlated with cancer risk, indicating that there is an association between eNOS 894G>T polymorphisms and an increased risk of developing cancer. Additionally, The significance of this association was further attributed to the specific type of polymorphism involved, as well as the risk of stroke in the T versus G model, followed by TT versus GG+GT. Conclusions: The eNOS 894G>T polymorphism showed a significant association with cancer and stroke risk. Specifically, the GT+TT model was associated with increased cancer risk compared to the GG model. This polymorphism also showed an association with stroke risk, with the T and TT models showing increased risk compared to the G and GG+GT models. These results suggest that the eNOS 894G>T polymorphism may be a potential risk factor for cancer and stroke.